Estimation of Crack Tip Position in Adhesively Bonded Joints Subjected to Mode II Fatigue Loading - M. Mehrabi; L. M. Martulli; A. Bernasconi; M. Carboni (Sensors)
Interest in adhesively bonded joints has significantly increased due to their numerous advantages over other joining techniques. However, they are frequently used in structures subjected to fatigue loading, which might cause defects such as cracks within the bondline. Thus, timely detection, localization, and size estimation of such defects are crucial for ensuring structural safety. This study focused on experimentally investigating crack length estimation in adhesively bonded joints under mode II fatigue loading. To analyze the crack growth, a comprehensive comparison was conducted between various techniques, such as visual testing, digital image correlation, optical backscatter reflectometry, and the analytical compliance-based beam method. In interrupted fatigue tests (static acquisition), digital image correlation and optical backscatter reflectometry exhibited consistent damage sensitivity, estimating larger crack lengths compared to visual testing by approximately 3 mm and 5 mm, respectively. The optical backscatter reflectometry in uninterrupted tests (dynamic acquisition) showed significantly larger estimations, approximately double those of static ones. This demonstrated its potential to detect possible damage within the adhesive that might not be detected by other methods, as shown previously for quasi-static loading conditions. Its capability in early damage detection under the dynamic regime makes it a valuable tool for continuous monitoring. Furthermore, a comparison of optical backscatter reflectometry’s performance in quasi-static, static, and dynamic acquisitions indicated a potentially larger process zone under quasi-static loading, a finding confirmed by the compliance-based beam method.